2020
DOI: 10.1017/s1759078720000185
|View full text |Cite
|
Sign up to set email alerts
|

Guided electromagnetic waves for damage detection and localization in metallic plates: numerical and experimental results

Abstract: Electromagnetic waves in the microwave and millimeter-wave frequency range are used in non-destructive testing and structural health monitoring applications to detect material defects such as delaminations, cracks, or inclusions. This work presents a sensing concept based on guided electromagnetic waves (GEW), in which the waveguide forms a union with the structure to be inspected. Exploiting ultra-wideband signals a surface defect in the area under the waveguide can be detected and accurately localized. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Even typical traditional nondestructive test (NDT) methods for various engineering structures including ultrasonic technology (Li et al, 2022), infrared thermography (Li et al, 2020), impact echo testing (Hsieh et al, 2016) and electromagnetic wave testing have shown their abilities in detecting common typical defects such as cracks in concrete and connection failure in steel structures, they are usually ineffective in interface debonding defects detection for CFST members (Castaner and Monni, 2020; Qiu, 2020). Interface debonding defects between fiber polymer and concrete in fiber polymer strengthened reinforced concrete (RC) columns can be sufficiently detected with electromagnetic (EM) wave method.…”
Section: Introductionmentioning
confidence: 99%
“…Even typical traditional nondestructive test (NDT) methods for various engineering structures including ultrasonic technology (Li et al, 2022), infrared thermography (Li et al, 2020), impact echo testing (Hsieh et al, 2016) and electromagnetic wave testing have shown their abilities in detecting common typical defects such as cracks in concrete and connection failure in steel structures, they are usually ineffective in interface debonding defects detection for CFST members (Castaner and Monni, 2020; Qiu, 2020). Interface debonding defects between fiber polymer and concrete in fiber polymer strengthened reinforced concrete (RC) columns can be sufficiently detected with electromagnetic (EM) wave method.…”
Section: Introductionmentioning
confidence: 99%
“…In [15], a sensing concept based on guided electromagnetic waves (GEW) is presented to detect material defects such as delaminations, cracks, or inclusions.…”
Section: Introductionmentioning
confidence: 99%